2018
DOI: 10.1111/1440-1630.12518
|View full text |Cite
|
Sign up to set email alerts
|

Learning from consumers: An eDelphi study of Australian mental health consumers’ priorities for recovery‐oriented curricula

Abstract: These findings highlight important capabilities from consumers' perspectives, suggesting key content for curricula. Active roles in designing, delivering and evaluating curricula were preferred, providing some guidance for educators seeking to involve consumers. Further research is required to refine these priorities, and to evaluate acceptability, feasibility and efficacy of varying modes of consumer involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 26 publications
0
39
0
Order By: Relevance
“…Where consumers were involved in the delivery of other content apart from their own stories (Table ), these topics were generally aligned with mental health consumer priorities for recovery‐oriented curricula (Arblaster et al, ). Academics seeking to further enhance consumers' involvement in occupational therapy curricula could work collaboratively with consumers and focus on the content areas highlighted by the Arblaster et al () study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where consumers were involved in the delivery of other content apart from their own stories (Table ), these topics were generally aligned with mental health consumer priorities for recovery‐oriented curricula (Arblaster et al, ). Academics seeking to further enhance consumers' involvement in occupational therapy curricula could work collaboratively with consumers and focus on the content areas highlighted by the Arblaster et al () study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that Australian mental health consumers were ready, willing and able to participate in occupational therapy education (Arblaster et al, ). Their preferred modes of participation span design, delivery and evaluation of curricula and included: (a) participating in simulations, (b) participating in advisory committees, (c) teaching in the classroom, (d) supporting curriculum design, (e) ‘telling my story’, (f) participating in program review committees, (g) taking up full‐ or part‐time academic roles, (h) assessing student presentations, (i) participating in research about mental health education in occupational therapy and (j) marking (Arblaster et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This study aimed to inform recovery-oriented mental health curricula in occupational therapy by articulating core capabilities for recovery-oriented occupational therapy practice from the perspective of mental health consumers. It builds on the findings of a previous study that identified consumers’ priorities for mental health curricula in pre-registration occupational therapy programmes (Arblaster et al., 2018). This information will assist occupational therapy educators to ensure curricula are designed to develop students’ capabilities for recovery-oriented practice.…”
Section: Introductionmentioning
confidence: 99%
“…Given the debate about recovery in the literature, and the policy emphasis on recovery-oriented practice, pre-registration occupational therapy education must engage with these concepts, and equip students to work in ways that acknowledge all factors contributing to mental distress and supporting recovery. However, there is limited guidance and no definitive set of capabilities for this type of practice in the occupational therapy literature (Arblaster et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation